EFL Higher Education Students’ Psychological Factor in Speaking Classroom Activities at Universitas Muslim Indonesia: A Research Report - Burhanuddin, Burhanuddin; Hudriati, Andi; Juniansyah, Dedi (Pascasarjana Universitas Negeri Makassar, 2023)
The aim of this study is to determine what types of psychological factors sixth-semester EFL higher education students confront when speaking English and how to overcome these psychological factors. This study employs qualitative descriptive methods with two variables. This research used the technique of purposive sampling to select participants, in which volunteers are chosen based on the criteria and objectives of the study. In this study, twenty 2019 Academic Foreign Language Student of the Sixth Semester participated. This research employed qualitative data analysis techniques (questionnaire). The score assigned to each student as a result. Using the Likert Scale Procedure, the data obtained from this study were analyzed. The findings revealed that the majority of students are affected by the same psychological factors, namely Anxiety, Lack of Self-Confidence, Fear, and Shyness. The majority of students are terrified of speaking English. They experience discomfort and agitation if they are required to answer or ask questions in English. Also, the results demonstrated that the sixth-semester ABA UMI class of 2019 possessed an extremely high degree of motivation. This is where they feel that learning English is crucial, since they are constantly asking their professors and peers about subjects they do not understand, and their desire to learn in English is quite strong. The study suggests that educators should focus on enhancing students' psychological factors, particularly motivation, anxiety, and self-confidence, to improve their speaking performance in the EFL classroom. The findings of this study contribute to the body of knowledge on the impact of psychological factors on EFL learners' speaking skills, and can help educators develop effective strategies to improve their students' speaking proficiency in the EFL classroom.